A COMPARATIVE STUDY BETWEEN WEIGHING AND IMAGE ANALYSIS TECHNIQUES FOR PREDICTING THE AMOUNT OF DEPOSITED ELECTROSPUN NANOFIBRES - Nurfaizey, A.H.; Long, F.C.; Daud, M.A.M.; Muhammad, N.; Masripan, N.A.; Tucker, N. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
Weighing and direct measurement are currently the two most common techniques used for estimating the amount of deposited nanofibres in electrospinning process. Nevertheless, due to its extremely small fibre size and mass, the task of measuring the weight or thickness of an electrospun nanofibres membrane is difficult and the results are arguable. This study evaluates the effectiveness of using greyscale image analysis for predicting the amount of deposited nanofibres compared to weighing technique. Polyvinyl alcohol electrospun nanofibres were collected at different deposition times on A4 black paper substrates. The substrates were weighed before and after deposition process and then scanned into 8 bit greyscale images. Analyses were carried out using ImageJ software, statistical analysis, high speed camera and scanning electron microscopy. At long deposition times, both techniques showed significant correlations between the measured values and deposition times. However, at short deposition times the weighing technique was found unreliable (p>0.05) compared to image analysis technique due to insignificant fibre masses compared to the weight variation of the substrates. Results suggest that image analysis technique was a better option to be used compared to weighing technique. This technique has the potential to be used as an automated online quality control in electrospun nanofibres manufacture.